2003
DOI: 10.1080/1071576021000036434
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Exposure of CC531 Rat Colon Carcinoma Cells Induces γ-glutamyltransferase which May Counteract Glutathione Depletion and Cell Death

Abstract: Gamma-glutamyltransferase (GGT) has a central role in glutathione homeostasis by initiating the breakdown of extracellular GSH. We investigated in the present study whether nitric oxide exposure of CC531 rat colon carcinoma cells modulates GGT and how the activity of the enzyme affects the level of intracellular GSH. The data show that GGT activity was induced in a dose-related manner by two NO-donors (spermineNONOate and nitrosoglutathione) and that antioxidants partly inhibited the induction. SpermineNONOate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…GGT and its relationship to redox balance in vivo has been thoroughly summarized by Whitfield [15], and several specific research findings provide a convincing rationale that increased GGT activity represents increased oxidative stress, including: GSH depletion appears to be a prerequisite condition to induce GGT [16];NADPH oxidase-produced reactive oxygen species and reactive nitrogen species both induce GGT expression [17,18];Mitochondria of GGT -knockout mice have depleted GSH, increased reactive oxygen species formation, depleted energy stores and impaired oxidative phosphorylation (thus impaired ATP production), which can be attenuated by N -acetylcysteine, a GSH precursor [19]; GGT -knockout mice die prematurely with complications associated with increased oxidative stress that can be attenuated with N -acetylcysteine [20]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GGT and its relationship to redox balance in vivo has been thoroughly summarized by Whitfield [15], and several specific research findings provide a convincing rationale that increased GGT activity represents increased oxidative stress, including: GSH depletion appears to be a prerequisite condition to induce GGT [16];NADPH oxidase-produced reactive oxygen species and reactive nitrogen species both induce GGT expression [17,18];Mitochondria of GGT -knockout mice have depleted GSH, increased reactive oxygen species formation, depleted energy stores and impaired oxidative phosphorylation (thus impaired ATP production), which can be attenuated by N -acetylcysteine, a GSH precursor [19]; GGT -knockout mice die prematurely with complications associated with increased oxidative stress that can be attenuated with N -acetylcysteine [20]. …”
mentioning
confidence: 99%
“…NADPH oxidase-produced reactive oxygen species and reactive nitrogen species both induce GGT expression [17,18];…”
mentioning
confidence: 99%
“…This may be the case of ZR-75-1 cells treated with S and Q, depending on GSH availability. Statistical association found between GSH-related and NO-related pathways might be because NO induces GGT to restore GSH and to prevent nitrosative death, as a feedback response (24). Thus, RNS/RSS balance might be decisive for antioxidant and cytoprotective effects of NO and GSH, respectively, with their reactive derivatives possibly interacting each other forming S-nitroso-metabolites and reciprocally cancelling their oxidative potential.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies with nitric oxide (NO) donors have demonstrated that the activity of the GGT enzyme in colon carcinoma cells is induced after exposure to NO and that the increase in GGT helped maintain intracellular GSH levels in cells grown in cystine-depleted medium by increasing substrate available for uptake into the cells [21]. Increased GGT activity thus acted to protect these cells against nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%